PENGARUH STRUKTUR KEPEMILIKAN TERHADAP FEE AUDIT - Fendra Deva Mahendra; Dul Muid (Diponegoro Journal of Accounting, 2017)
The purpose of this paper is to investigate the association between corporate ownership structures and audit fees paid to external auditors by Indonesian companies listed on Bursa Efek Indonesia (BEI). This study focusses on the extent of the auditor’s reliance on the client’s internal control inasmuch as the corporate ownership structures are varied, and, ultimately, affect the audit fees. This study applies the agency theory in formulating three hypotheses that guide the results analysis. By employing a multi regression model for a sample of 133 Indonesian companies listed on Bursa Efek Indonesia (BEI), this study examines the relationship of ownership structure, namely, managerial ownership, foreign ownership and government ownership with audit fees using data for 2015. The results show a significant positive relationship between audit fees and firms with larger foreign ownership and higher government ownership. However this study shows negative but insignificant relationship with firms with higher managerial ownership. This study contributes recent evidence concerning the relationship between corporate ownership structure and audit fees.